DOES MALE GENDER INCREASE THE RISK OF LAPAROSCOPIC CHOLECYSTECTOMY? - COELHO, Júlio Cezar Uili (Arq Bras Cir Dig, 2019)
BACKGROUND: Laparoscopic cholecystectomy is the preferable treatment for chronic or acute cholecystitis. Some factors may increase the rate of laparoscopic conversion to open cholecystectomy and perioperative complications. The role of gender as a risk factor for laparoscopic cholecystectomy is controversial. AIM: To evaluate the role of the gender on the operative findings and outcome of laparoscopic cholecystectomy. METHOD: All patients who underwent laparoscopic cholecystectomy for chronic or acute cholecystitis were included. Demographic, clinical, laboratory, imaging exams, intraoperative and postoperative data were obtained and analyzed. The data was obtained retrospectively from electronic medical records and study protocols. RESULTS: Of a total 1,645 patients who were subjected to laparoscopic cholecystectomy, 540 (32.8%) were men and 1,105 (67.2%) were women. Mean age was similar in both genders (p=0.817). Operative time has longer in the male (72.48±28.50) than in the female group (65.46±24.83, p<0.001). The rate of acute cholecystitis was higher in the male (14.3%) than in the female group (5.1%, p<0.001). There was no difference between the genders in regard to the rate of conversion (p=1.0), intraoperative complication (p=1.0), postoperative complication (p=0.571), and operative mortality (p=1.0). CONCLUSION: Male gender is not an independent risk factor for laparoscopic conversion and perioperative complications.